Pre-competition anxiety levels among Rahim Kajai college athletes in intercollegiate sports competitions - Jackson Jastari; Mohamad Nizam Nazarudin; Zakiah Noordin (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study was conducted to identify the level of anxiety of Kolej Rahim Kajai (KRJ) athletes before the residential college sports competition. A total of 144 athletes consisting of 78 male athletes and 66 female athletes were randomly selected using probability sampling to answer a questionnaire. The ‘Competitive State Anxiety Inventory-2’ (CSAI-2) questionnaire which was created by Cox & Russel (2003) was used to see the level of anxiety before a sports competition involving three aspects, namely cognitive anxiety, somatic anxiety, and self-confidence. The mean score and standard deviation are consulted to find out whether the interpretation is at a low, medium, or high level. The results of this study found that UKM KRJ athletes have a high level of cognitive anxiety (M=3.00, SP=0.41), moderate somatic anxiety (M=2.40, SP=0.77), and a moderate level of self-confidence (M=2.90, SP=0.32) before the competition. The results of the t-test showed that there was no significant difference in the level of cognitive anxiety (p=0.321), the level of somatic anxiety (p=0.220), and self-confidence (p=0.254) between genders. The study also found that there was no significant difference in the level of cognitive anxiety (p=0.813), the level of somatic anxiety (p=0.60), and self-confidence (p=0.29) between individual and group sports. The results of this study can be used as a guide to plan training for KRJ athletes in order to improve their performance during competitions in the future. This study also suggests training needed to deal with pre-competition anxiety and lack of self-confidence.